7SL RNA and signal recognition particle orchestrate a global cellular response to acute thermal stress - Bojan Bujisic; Hun-Goo Lee; Lilei Xu; Uri Weissbein; Carlos Rivera; Ivan Topisirovic; Jeannie T. Lee (Nature Communications)
Abstract Non-coding 7SL RNA is an ancestor to mammalian Alu and B1 SINE RNAs and is thought to function exclusively within the Signal Recognition Particle (SRP), aiding in the translocation of secretory proteins into the endoplasmic reticulum for export. Here, we discover a function of 7SL/SRP unrelated to protein secretion. Under acute heat shock, 7SL and SRP together selectively arrest cellular transcription and translation machineries during early response to stress. Under thermal stress, 7SL is upregulated, accumulates in the nucleus, and binds to target genes repressed by heat shock. Concurrently, in the cytosol, SRP binds to ribosomes and inhibits new protein synthesis. Translational suppression occurs independently of the signal peptide and is abrogated by depleting SRP. Translation inhibition extends to the mitochondria, as nuclear-encoded genes with mitochondrial functions are enriched among SRP targets. Thus, apart from its role in protein export, 7SL/SRP orchestrates a global response to acute stress that encompasses the nucleus, cytosol, and mitochondria across transcription and translation.